The Impact of COVID-19 and Pandemic Mitigation Measures on Persons With Sensory Impairment - Bernard, Alec (Am J Ophthalmol, 2022)
PURPOSE: To assess the impact of the COVID-19 pandemic and associated mitigation measures on persons with sensory impairments (SI), including visual impairments (VI) and hearing impairments (HI). DESIGN: Cross-sectional survey. METHODS: Adults with VI (best-corrected visual acuity <20/60 in the better-seeing eye), HI (International Classification of Diseases, Tenth Revision, codes), and age- and sex-matched controls (n = 375) were recruited from the University of Michigan. The 34-item Coronavirus Disability Survey was administered. Both χ(2) tests and logistic regression were used to compare survey responses between groups. RESULTS: All groups reported high levels of disruption of daily life, with 80% reporting “a fair amount” or “a lot” of disruption (VI: 76%, HI: 83%, CT: 82%, P = .33). Participants with VI had greater difficulty with day-to-day activities and were more likely to cite the following reasons: caregiver was worried about COVID-19 (odds ratio [OR](VI) = 7.2, 95% CI = 3.5-14.4, P < .001) and decreased availability of public transportation (OR(VI) = 5.0, 95% CI = 1.5-15.6, P = .006). Participants with VI, but not HI, showed a trend toward increased difficulty accessing medical care (OR(VI) = 2.0, 95% CI = 0.99-4.0, P = .052) and began relying more on others for day-to-day assistance (OR(VI) = 3.1, 95% CI = 1.6-5.7, P < .001). Overall, 30% reported difficulty obtaining trusted information about the pandemic. Those with VI reported more difficulty seeing or hearing trusted information (OR(VI) = 6.1, 95% CI = 1.6-22.1, P = .006). Employed participants with HI were more likely to report a reduction in wages (OR(HI) = 2.5, 95% CI = 1.2-5.3, P = .02). CONCLUSIONS: Individuals with VI have experienced increased disruption and challenges in daily activities related to the pandemic. People with SI may benefit from targeted policy approaches to the current pandemic and future stressors. Minimal differences in some survey measures may be due to the large impact of the pandemic on the population as a whole. The SARS-CoV-2 (COVID-19) pandemic and public health mitigation measures have had an exceedingly large impact around the globe. As of the time of writing, more than 114 million global cases (28 million US) had been diagnosed, and there had been more than 2.5 million fatalities attributed to COVID-19 (517,000 US).(1)(,)(2)